DIVERSIDADE CARIOTÍPICA EM ESPÉCIES DO GÊNERO Astyanax (TELEOSTEI, CHARACIDAE) OCORRENTES NO MÉDIO RIO IGUAÇU - Dulz, Thaís Aparecida (2015)
The Characidae is considered the largest family and most complex among the Characiforms. The Astyanax genus is one of the most specious between the characids, comprising 142 valid species distributed in the Neotropical Region. Many of these species are restricted to certain river basins. The fish fauna of the Iguaçu River basin is characterized by having a high endemism, possibly because its isolation of the Paraná River basin, occurred about 22 million years, caused by the emergence of the Iguaçu Falls. Were recently described new species of this genus in the Rio Iguaçu, however its systematic position opposite the other Astyanax is still unknown, reinforcing necessary studies aimed at understanding their diversity and their evolutionary relationships. Therefore, this research aimed was to perform the karyotype characterization of the Astyanax species from the middle Rio Iguaçu: Astyanax altiparanae, A. bifasciatus, A. dissimilis, A. minor, A. ribeirae and A. serratus, using cytogenetics as a tool, in order to contribute to a more consistent scenario about the evolution of this group. The analysis were based on conventional Giemsa staining techniques, detection of nucleolar organizing regions by silver nitrate (Ag-NORs), C-banding and fluorescence in situ hybridization (FISH) to ribosomal genes 18S e 5S probes. All species presented 2n = 50 chromosomes, confirming the conservatism to the genus. The karyotypes comprise all chromosomal types and prevalence of chromosomes with two arms, mainly on the metacentric type except for A. ribeirae with the karyotype formula containing high number of acrocentrics. Despite the diploid number remain constant in these species; there were variations in karyotype formula and consequently the fundamental number, ranging from 66 to 92. The C-banding showed differences in the distribution of heterochromatic blocks between species, occurring polymorphism in A. serratus, which was also observed in other studies involving Astyanax sp. D (A. serratus). The six species showed the presence of NORs located in the telomeric region of the short arm of a chromosome pair of the type subtelocentric, characteristic conserved for the genus. Was identified single NORs in A. altiparanae and A. dissimilis, although the most common being multiple NORs, in almost all cases confirmed by 18S rDNA. All species showed 5S rDNA located in the interstitial segments of the chromosomes. Have been observed simple rDNA 5S in A. altiparanae, A. minor and A. serratus, and multiple in A. bifasciatus, A. dissimilis and A. ribeirae. Highlighted A. ribeirae by presenting a high number of rDNA 18S and 5S sites, which proved to be sintenics and co-located. In addition, this species is considered endemic for Ribeira de Iguape basin; however, was first found in the Iguaçu basin, strengthening fauna sharing hypothesis between rivers of the plateau and coastal regions in southern Brazil. The karyotype diversity evident for all species is mainly due to non-Robertsonian rearrangements. This study presented the first cytogenetic data for the genus Astyanax occurring in the Middle Rio Iguaçu region.